Formulation and Evaluation of herbal multipurpose cream - Aishwarya Y. Patil Patil; Urmila C Patel; Madhuri A. Patel; Amit Kumar R. Dhankani; Sunil P. Pawar (Recent Trends in Cosmetics, 2024)
Multipurpose creams are semi-solid preparations used to lower the risk of skin disorders and fight wrinkles. The primary goal of the research is to produce multipurpose creams utilizing various herbs and then analyze their efficacy. The herbs utilized in the preparations include dried bael leaf powder, amla powder, neem powder and bael leaves. The article emphasizes the importance of topical drug delivery systems in dermatology, highlighting the benefits of delivering medications directly to the skin for localized treatment. Various types of cream formulations, categorized as oil-in-water (O/W) and water-in-oil (W/O) emulsions, are discussed along with their specific uses and properties. The use of natural ingredients in creams is encouraged instead of additives to promote safe and environmentally friendly skin care products. Furthermore, the article reviews specific botanical extracts such as Aegle marmelos (Bael), Emblica officinalis (Amla), and Azadirachta indica (Neem), known for their medicinal properties in skincare. These extracts are analyzed for their chemical compositions and therapeutic benefits, highlighting their potential applications in herbal cosmetic formulations. The study concludes by discussing the importance of cosmetic products in skincare routines and explaining their therapeutic use and procedures. It advocates for the development of natural and herbal-based skincare products to meet consumer demand for safer and effective cosmetic solutions. "The multifunctional creams underwent various tests including irritancy, washability, pH, viscosity, phase separation, spreadability, and compatibility assessments. The results indicated that each formulation yielded favorable outcomes."
Keywords: Acne; Antifungal; Bael; Cosmetic; Dermatitis; Multipurpose